Homozygosity mapping of autosomal recessive intellectual disability loci in 11 consanguineous Pakistani families. Issue 1 (1st December 2014) - Ahmed, Iltaf; Rafiq, Muhammad Arshad; Vincent, John B.; Bhatti, Attya; Ayub, Muhammad; John, Peter
Abstract : Background: Autosomal recessive intellectual disability (ID) is genetically heterogeneous and most of the genes causing it remain undiscovered. Objective: We have ascertained 11 consanguineous families multiplex for IDs in order to identify new loci for autosomal recessive genes for non-syndromic ID, or to aid pinpointing mutations in known causative gene/loci. Methodology: Microarray genotyping (Affymatrix 250K) was performed to identify homozygosity-by-descent (HBD) in all affected families. Results: Analysis of genotypes revealed 45 potential HBD regions across the families, although these may be rationalised down to 39. Two families share an overlapping HBD region on 7q11.21. In one family, X-linkage also looks plausible, and a new ID gene near the centromere may be a likely cause. In one family, no HBD region was found, and thus we exclude autosomal recessive mutation as the likely cause in this family. Copy-number variation (CNV) was also performed and revealed no CNVs, homozygous or heterozygous, segregating with the phenotype. Conclusion: The homozygous loci identified in this study might harbour candidate genes for ID in these studied families. Therefore, we are proceeding with next-generation sequencing analysis of the families, using whole-exome approaches, and anticipate that this will identify the causative gene/mutation within the identified HBD regions for many of the families studied here.